Arnold Toynbee and the Process of Civilizations - Dombrowski, Daniel A. (Cosmos and History: The Journal of Natural and Social Philosophy, 2021)
It is now common to hear discourse about “the decline of civilization” and to learn about people’s fears that civilization might even be on the verge of collapse. In one sense, such discourse is nothing new in that at least since the time of Oswald Spengler and World War One there have been concerns and/or predictions about the decline (and perhaps fall) of “the West.” But in another sense, there are more proximate causes for the recent popularity of decline and fall discourse. It will serve us well, I think, to reconsider a thinker who thought long and hard about the rise and fall of civilizations in the past, Arnold Toynbee. It will be the purpose of the present article to argue for the claim that Toynbee can be fruitfully seen as a process thinker who was specifically concerned with the dramatic changes that have occurred historically to various civilizations around the globe. In this regard, he is in many ways a philosopher or historian of civilization, much like Alfred North Whitehead, Henri Bergson, and Teilhard de Chardin, all of whom are cited favorably by Toynbee. He is also similar to the process philosopher Charles Hartshorne in this regard. I will claim that Toynbee can provide valuable insight to us at this moment in history. That is, the sense that civilized life is threatened is not a new phenomenon, hence it will be useful to consider Toynbee’s scholarship so as to help us gain some much-needed historical perspective on civilizational change.